2021
DOI: 10.1016/j.omtn.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of tRNA-derived RNA fragments in human pathophysiology

Abstract: Hundreds of tRNA genes and pseudogenes are encoded by the human genome. tRNAs are the second most abundant type of RNA in the cell. Advancement in deep-sequencing technologies have revealed the presence of abundant expression of functional tRNA-derived RNA fragments (tRFs). They are either generated from precursor (pre-)tRNA or mature tRNA. They have been found to play crucial regulatory roles during different pathological conditions. Herein, we briefly summarize the discovery and recent advances in decipherin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…The roles of tiRNAs in relevant pathways such as NF-κB, IFN, and Wnt/β-Catenin also suggest their role in immune responses [95]. For instance, the activation of Toll-like receptor 4 (TLR-4) with bacterial lipopolysaccharides (LPS) induces a signalling cascade that enhances NF-κB activation and promotes the expression of ANG exonuclease.…”
Section: Role Of Tirna On Immunity and Their Potential As Cross-speci...mentioning
confidence: 99%
“…The roles of tiRNAs in relevant pathways such as NF-κB, IFN, and Wnt/β-Catenin also suggest their role in immune responses [95]. For instance, the activation of Toll-like receptor 4 (TLR-4) with bacterial lipopolysaccharides (LPS) induces a signalling cascade that enhances NF-κB activation and promotes the expression of ANG exonuclease.…”
Section: Role Of Tirna On Immunity and Their Potential As Cross-speci...mentioning
confidence: 99%
“…tRNA-derived fragments (tRFs) are short non-coding RNAs derived from tRNA, approximately 16–40 nucleotides in length [ 5 ], which originate from mitochondrial or nuclear tRNAs [ 6 ]. Currently, tRFs are known to be involved in various physiological and pathological processes, such as infectious diseases and tumor formation, and in neurodegenerative diseases [ 7 ]. Schimmel reported that the events of tRF production responded to many stresses such as hyperosmotic stress, pro-oncogenic transcription under hypoxia, and regulation of hematopoiesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypo-modified tRNAs can also become better substrates for RNase cleavage leading to tRNA fragment generation ( Huang and Hopper, 2016 ; Oberbauer and Schaefer, 2018 ). tRNA fragments are a family of small RNAs that participate in many regulatory processes at the cellular and organismal levels ( Anderson and Ivanov, 2014 ; Schimmel, 2018 ; Pandey et al, 2021 ). In the context of viral infections, tRNAs as well as tRNA fragments may facilitate viral replication ( Jin and Musier-Forsyth, 2019 ; Nunes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%